Who is Writing? Author Affiliation across Peer-Reviewed Journals of Emotional or Behavioral Disorders, 2000–2011. (February 2013) - Schoenfeld, Naomi A.; Janney, Donna M.; Rekart, Jerome L.
The importance of practitioner participation in identifying and maintaining use of best educational practice is well established; however, little is known about the ways in which practitioners contribute to the development and dissemination of those practices within the field of emotional or behavioral disorders (EBD). This review examines patterns of authorship affiliation across journals with a primary audience of direct service providers working with students with EBD published from January 2000 through December 2010. Authors associated with institutions of higher education represented 79.8% (n = 2590) of affiliations, with practitioners comprising only 5.1% (n = 164) of all listed affiliations. Practitioners were most likely to be authors or coauthors on informative articles or reports. The implications of these findings for policy and practice are discussed.